Health effects of ruminant trans fatty acids with emphasis on type 2 diabetes - Xu, Yanqing; Dugan, Michael E. R.; Mapiye, Cletos; Vahmani, Payam (Frontiers in Animal Science, 2023)
Recent government bans on industrial trans fatty acids (TFA) in developed countries has left naturally occurring TFA from ruminant products (e.g., dairy, beef, and lamb) as the sole source of TFA in the food supply. In contrast to industrial TFA, which have undisputed adverse health effects, ruminant TFA such as trans vaccenic acid (TVA; trans11-18:1), rumenic acid (RA; cis9, trans11-18:2) and trans palmitoleic acid (TPA; trans9-16:1) have been associated with reduced risk for some diseases such as type 2 diabetes. The present review summarizes the findings from observational, animal and human studies investigating the effects of ruminant TFA on metabolic parameters related to type 2 diabetes, and provides an update on the current knowledge of their biosynthesis, intake and factors affecting their concentrations in ruminant derived foods. Overall, observational studies and a small number of animal studies suggest that ruminant TFA may be protective against type 2 diabetes, whereas the same benefits have not been observed in other animal studies or in human clinical trials. Additional clinical and mechanistic studies are needed to better understand the isomer-specific effects of ruminant TFA. Until then, production practices resulting in increased levels of this group of fatty acids in ruminant milk and meat should be carefully reconsidered.